P053: Mismatches in pre-injury activities and return-to-activity advice received by concussion patients presenting to the emergency department. (May 2019) - Gaudet, L.; Eliyahu, L.; Mrazik, M.; Beach, J.; Cummings, G.; Voaklander, D.; Rowe, B.
Abstract : Introduction : Patients with concussion often present to the emergency department (ED). Current guidelines recommend graded return to work and physical activity (i.e., sport, recreation and exercise activities); however, whether emergency physicians target this advice based on patient-reported activities is unknown. This study aimed to assess mismatches between physicians' rest and return-to-activity advice and self-reported pre-injury work and physical activity of adult concussion patients.Methods : Adults (>17 years) presenting with a concussion from April 2013 to April 2015 to a study ED with Glasgow coma scale score ≥13 were recruited by on-site research assistants. Data on patient characteristics (i.e., age, sex, employment, and physical activity level) and activity leading to injury were collected from structured patient interviews. A structured questionnaire collected data from the treating physician about discharge advice provided. "Working" was defined as employed or enrolled in any level of school at the time of injury. "Physically active" was defined by reporting regular exercise (≥2 times a week) or concussed during a sports-related activity. Proportions or medians (interquartile range [IQR]) are reported, as appropriate.Results : Physician questionnaires were completed for 198/248 enrolled patients (median age: 37 years [IQR: 23, 49]; 46% male). Overall, 89% (177/198) were working; 110/177 (62%) received return-to-work advice, while 10/21 (48%) patients also received return-to-work advice, despite not working. Mentally strenuous work/school duties were reported by 143 patients, of which 85 (60%) were recommended cognitive rest. Overall, 148 patients were physically active and 115 (78%) of these were recommended physical rest while 124 (82%) were advised on safe return to physical activity. On the other hand, 35/50 (70%) patients who were not physically active received advice on safe return to physical activity. Sustaining a sports-related injury significantly increased the likelihood of safe return to physical activity advice among physically active patients (Fisher's exact p = 0.001).Conclusion : There is a mismatch between concussed patients' pre-injury activities, and the rest and return-to-activity (i.e., work and physical activity) advice provided by emergency physicians. The possible effect of this mismatch on patient outcomes should be assessed in future research, as should strategies to improve emergency physician-patient communications around concussion management.